Factors that Promote Reading Culture and Its Impact on Society - Khairul Nizam bin Zainal Badri (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
From time immemorial, books have had a very intimate relationship in human life. Books are considered a symbol of civilization because of their relationship to reading habits. This is because the habit is an effort to develop human potential through the addition of knowledge. Doing research on the book industry is an interesting thing, because its development in line with technology is amazing. For example, today, reading material in the form of audio-books is increasingly gaining the attention of the world community. Nevertheless, books in physical form still have sentimental value in the hearts of readers, and still dominate the world market. Using a library approach through data collection on the website, this study examines the development of the book industry and its relationship with reading culture in Malaysia. In addition, factors that promote reading culture were also identified. In conclusion, efforts to increase the publication of books and cultivate the community with book activities must be continued and support from all parties must be done so that books can be fully utilized by the community.